The meta-analysis of the effect of 68Ga-PSMA-PET/CT diagnosis of prostatic cancer compared with bone scan. Issue 15 (16th April 2021) - Zhao, Ruining; Li, Yajie; Nie, Lihong; Qin, Kaiyue; Zhang, Hang; Shi, Hongbin
Abstract: Background: 68 Ga-PSMA-PET/CT (positron emission tomography/computed tomography) is a promising method for prostate cancer (PC) detection. However, the ability of 68 Ga-PSMA-PET/CT to detect malignant bone lesions, and whether this method is superior to the existing bone imaging methods are still lack of systematic analysis. Purpose: To evaluate the value of 68 Ga-PSMA-PET/CT and bone scan in clinical diagnosis of prostatic cancer from the perspective of evidence-based medicine. Methods: PubMed, The Cochrane Library, EMBASE, Springer Link, Sinomed, CNKI, Wanfang database, and CQVIP database were searched to find the satisfactory studies that needed systematic review of trials and compared the value of 68Ga-PSMA-PET/CT and bone scan. All studies published from inception to March 31, 2020. According to the inclusion and exclusion criteria, 2 reviewers independently evaluated and extracted the literature. Review Manager 5.3 was applied to evaluate the included literature quality. The heterogeneity of the included literature was tested by Meta Disc 1.4, and the effect model was selected according to the heterogeneity test results, and the sensitivity (SEN), specificity (SPE), PLR, NLR and diagnostic odds ratio (DOR) were analyzed. After testing the heterogeneity results of literature by using the 95% confidence interval and the forest map. Results: A total of 4 studies were eligible for inclusion in the meta-analysis, which included 318 patients, 120 cases with bone metastasis and 198 cases without bone metastasis. The results of summary evaluation for 68 Ga-PSMA-PET/CT and bone scan in diagnosis of prostatic cancer as follow respectively: The SEN were 0.97 and 0.86; the SPE were 1.00 and 0.87; the DOR were 1468.33 and 36.23; PLR were 88.45 and 6.67; NLR were 0.05 and 0.19; and the area under curve (AUC) and 95% CI were 0.9973 (1.0000–0.9927) and 0.8838 (0.9584–0.8092). Conclusion: By comparing the diagnostic results of 68 Ga-PSMA-PET/CT and bone scan imaging diagnosis methods, the 68 Ga-PSMA-PET/CT has a higher SEN and SPE than bone scan, and it has a higher diagnostic efficiency for prostate cancer bone metastasis, which is worthy of clinical application.